Solid Polymeric Nanoparticles of Albendazole: Synthesis, Physico-Chemical Characterization and Biological Activity - Roxana Racoviceanu; Cristina Trandafirescu; Mirela Voicu; Roxana Ghiulai; Florin Borcan; Cristina Dehelean; Claudia Watz; Zoltán Aigner; Rita Ambrus; Dorina Elena Coricovac; Denisa Cîrcioban; Alexandra Mioc; et al. (Molecules, 2020)
Albendazole is a benzimidazole derivative with documented antitumor activity and low toxicity to healthy cells. The major disadvantage in terms of clinical use is its low aqueous solubility which limits its bioavailability. Albendazole was incorporated into stable and homogeneous polyurethane structures with the aim of obtaining an improved drug delivery system model. Spectral and thermal analysis was used to investigate the encapsulation process and confirmed the presence of albendazole inside the nanoparticles. The in vitro anticancer properties of albendazole encapsulated in polyurethane structures versus the un-encapsulated compound were tested on two breast cancer cell lines, MCF-7 and MDA-MB-231, in terms of cellular viability and apoptosis induction. The study showed that the encapsulation process enhanced the antitumor activity of albendazole on the MCF-7 and MDA-MB-23 breast cancer lines. The cytotoxic activity manifested in a concentration-dependent manner and was accompanied by changes in cell morphology and nuclear fragmentation.